Implementation of Memetic Algorithms into Structural Optimization - Peter Pechac; Milan Saga; Ardeshir Guran; Leszek Radziszewski (Communications - Scientific letters of the University of Zilina, 2016)
The paper presents an implementation of the memetic algorithm for discrete structural optimization. This algorithm is a combination of genetic algorithm and five local search methods. The proposed memetic algorithm is able to choose the right local search method based on performance which is evaluated in real time during optimization.